Flexural uplift and magmatic underplating anomaly on the Argentine continental margin: profile at 43.5°S - Pedraza De Marchi, Ana Carolina (2021)
Magmatic underplating can be defined as the addition of mafic magma to the lower crust and uppermost mantle around the Moho. This phenomenon plays an important role in continental margins and other compressional and extensional tectonic environments. We have modeled the magmatic underplating effect using Process-Oriented Gravity Modeling (POGM) along a profile at 43.5°S on the Argentine continental margin, which re-thickens the crust and causes uplift. In POGM, the gravity anomaly is formed by the rift, sedimentation, and magmatic underplating anomaly. This work focuses on the flexural uplift produced by the magmatic underplating and its gravity anomaly, rarely investigated in margins since seismic refraction data is generally unavailable to the scientific community. Particularly, it has not been calculated in the volcanic sector of the Argentine continental margin before this work. The results yield an average maximum flexural uplift associated with magmatic underplating, which is um = 140.32 m ± 22.12 m, an average density of the underplated body of ρx = 3133.89 kg/m3 ± 22.71 kg/m3, and an average density of the sediment ρs = 2207.78 kg/m3 ± 42.58 kg/m3 and an average oceanic crustal thickness of 6.36 km. The average elastic thickness leaving out the magmatic underplating effect is Te = 24 km ± 2.02 km, and including it is Te = 33.89 km ± 2.35 km. The magmatic underplating anomaly has an opposite contribution to the typical free-air gravity edge-effect for the Airy and flexural cases.